ON RICCI SOLITONS IN (????)-KENMOTSU MANIFOLDS (International Journal of Engineering Sciences & Management Research, 2018)
The object of the present paper is to study Ricci solitons in ( ???? )-Kenmotsu manifolds satisfying S(X,????).R=0,R(????,X).P =0, P(????,X).R=0, R(????, ????).???? ̅ =0, and ???? ̅(????, ????).S=0, where P is projective curvature tensor and ???? ̅ is pseudo-projective curvature tensor. 2010, Mathematics Subject Classification: 53C25,53C15..